Addressing the cancer burden in LMICs: the potential of modulated electro-hyperthermia - Minnaar, Carrie Anne; Hugo, Mia; Pillay, Prinitha; Naidoo, Thanushree; Kotzen, Jeffrey Allen; Ramiah, Duvern (Frontiers in Oncology, 2025)
Cancer in low- and middle-income countries (LMICs) is associated with late-stage diagnoses and poor survival, compounded by limited access to screening, diagnostic tools, and treatment. The high prevalence of HIV further complicates outcomes, especially in sub-Saharan Africa. Hyperthermia has emerged as a valuable adjunct to treatment in high-income countries, particularly for locally advanced cancers such as cervical and head and neck tumours, which are common in resource-constrained settings. Uptake of hyperthermia in LMICs has however been limited. A phase III randomised controlled trial in a South African public hospital demonstrated that modulated electro-hyperthermia (mEHT), a capacitively coupled heating technique, was feasible in this setting. The trial, the first to assess hyperthermia in Africa and to include HIV-positive participants, found that adding mEHT to chemoradiotherapy significantly improved 5-year disease-free survival (32% vs. 14%; HR:0.73; 95%CI:0.53-1.00; p=0.049); reduced recurrence, and improved quality of life without increasing toxicity. Benefits were observed equally in HIV-positive and HIV-negative participants. A cost-effectiveness analysis indicated an 82.2% probability of cost savings over three years, primarily due to fewer recurrences and residual disease and improved quality of life. Given its affordability, ease of integration, and lack of additional toxicity, mEHT represents a promising adjunct to chemoradiation in LMICs. Further replication in LMICs beyond sub-Saharan Africa is needed to confirm generalisability to diverse healthcare settings.